2013
DOI: 10.1080/14616734.2013.746822
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dialogues of foster caregivers with their children: the role of the caregivers, above and beyond child characteristics, in shaping the interactions

Abstract: The study examined foster caregivers' sensitive guidance of conversations about emotional themes in a sample of foster caregivers living in Family Group Homes. Thirty caregivers were observed with two out of the several children under their care: one that was nominated by the Family Group Home's social worker as the most challenging child in the Family Group Home, and one that was nominated as the least challenging child. Based on attachment theory that argues that mothers possess a central role in shaping the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The majority of prior research regarding emotional dialogues focused on early childhood (e.g., Fivush, Haden, & Reese, 2006;Koren-Karie et al, 2003), and indicated that the co-construction of conversations about emotional experiences help children learn how to process emotional experiences, share them with others, and cope with similar socioemotional situations (Fivush, Berlin, McDermott-Sales, Menuti-Washburn, & Cassidy, 2003;Koren-Karie et al, 2003). Our study joins the relatively few works on parent-child emotional dialogues in adolescence (e.g., Bohanek et al, 2008;Koren-Karie, Oppenheim, Yuval-Adler, & Mor, 2013;McLean & Jennings, 2012;McLean & Mansfield, 2012). Together, this line of research suggests that daily conversations with parents about emotional experiences are an arena in which an intergenerational transmission of information processing rules and regulation of emotional experiences occurs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The majority of prior research regarding emotional dialogues focused on early childhood (e.g., Fivush, Haden, & Reese, 2006;Koren-Karie et al, 2003), and indicated that the co-construction of conversations about emotional experiences help children learn how to process emotional experiences, share them with others, and cope with similar socioemotional situations (Fivush, Berlin, McDermott-Sales, Menuti-Washburn, & Cassidy, 2003;Koren-Karie et al, 2003). Our study joins the relatively few works on parent-child emotional dialogues in adolescence (e.g., Bohanek et al, 2008;Koren-Karie, Oppenheim, Yuval-Adler, & Mor, 2013;McLean & Jennings, 2012;McLean & Mansfield, 2012). Together, this line of research suggests that daily conversations with parents about emotional experiences are an arena in which an intergenerational transmission of information processing rules and regulation of emotional experiences occurs.…”
Section: Discussionsupporting
confidence: 74%
“…The current study builds on prior research documenting parenting effects. In a study of mothers and their foster children (Koren‐Karie et al., ), mothers' sensitive guidance of emotional dialogues was assessed twice, once with their most challenging foster child, and once with their least challenging foster‐child. Results showed that mothers' sensitive guidance was similar across the most and least challenging foster‐children, which supports the notion that parents shape the emotional dialogues with their child.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the foster care study mentioned earlier (Koren-Karie et al, 2012), in which mothers who fostered several children were assessed with the most and least challenging child under their care, we observed the mothers during emotion dialogues with the children (in addition to obtaining IA assessments as described earlier). We hypothesized that because emotion dialogues are strongly influenced by the parent's capacity to sensitively guide the dialogue in a way that is matched to the child's emotions, needs, and competencies, mothers' guidance of the dialogues with both children would be similar, even though the children were selected to present different -and highly contrastive -levels of challenge.…”
Section: Empirical Research On Mother-child Emotion Dialoguesmentioning
confidence: 99%
“…Although this result needs to be interpreted with caution, because of small sample sizes of the samples in which only one partner had been exposed to trauma, this is an interesting finding. One would expect that mothers, who are the mature and experienced partner of the dyad, will have more impact on the conversation than the child, which has been found before [32]. Trauma-exposure however may have such a great influence that the dyad as a whole is negatively influenced, regardless of which partner was exposed to the traumatic events.…”
Section: Discussionmentioning
confidence: 89%